'A Procedure Without a Problem', or the face transplant that didn't happen. The Royal Free, the Royal College of Surgeons and the challenge of surgical firsts. Issue 3 (12th October 2021) - Bound Alberti, Fay; Hoyle, Victoria
Abstract : Face transplants are an innovative and unusual form of modern surgery. There have been 47 face transplants around the world to date, but none as yet in the UK. Yet in 2003, the UK was poised to undertake the first face transplant in the world. The reasons why it didn't take place are not straightforward, but largely unexplored by historians. The Royal College of Surgeons, concerned about the media attention given to face transplants and the ethical and surgical issues involved, held a working party and concluded that it could not give approval for face transplants, effectively bringing to a halt the UK's momentum in the field. This extraordinary episode in medical history has been anecdotally influential in shaping the course of British surgical history. This article explores and explains the lack of a face transplant in the UK and draws attention to the complex emotional, institutional and international issues involved. Its findings have implications beyond the theme of face transplants, into the cultural contexts and practices in which surgical innovation takes place.